2018
DOI: 10.1097/wnn.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Patients with Early Parkinson Disease on an Executive and Social Cognition Battery

Abstract: Objective: To demonstrate the usefulness of incorporating the Executive and Social Cognition Battery (ESCB) to detect executive and social cognition deficits, which are otherwise not captured by more “classical” executive tests in early Parkinson disease (PD). Background: PD is a neurodegenerative disorder that includes executive and social cognition deficits. While cognitive assessment in PD still relies on classical executive tasks to detect frontal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…Patients could present MCI only (MoCA < 26) or SCI only (Mini-SEA < 23.1). The independence of social cognition deficit from other cognitive impairments was recently reported 27 . Esteves al (2018) 27 found that 38.5% of patients with early PD showed impairment on social cognitive tests only and not on executive tests, whereas 12.8% showed impairment on executive tests only and not on social cognitive tests in a smaller group of patients (N=39).…”
Section: [Insert Figure 1] Discussionmentioning
confidence: 90%
“…Patients could present MCI only (MoCA < 26) or SCI only (Mini-SEA < 23.1). The independence of social cognition deficit from other cognitive impairments was recently reported 27 . Esteves al (2018) 27 found that 38.5% of patients with early PD showed impairment on social cognitive tests only and not on executive tests, whereas 12.8% showed impairment on executive tests only and not on social cognitive tests in a smaller group of patients (N=39).…”
Section: [Insert Figure 1] Discussionmentioning
confidence: 90%
“…Moreover, mild cognitive impairment represents a significant risk factor for early dementia (77). Frontal dysfunction has also been noted using the executive and social cognition battery (78).…”
Section: Cognition Symptomsmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to evaluate detailed social cognition with all social cognitive domains in PD in the Indian context. Given the cultural sensitivity of instruments used to assess social cognition, it is important to generate data from diverse and underrepresented social groups, particularly as impairments in this domain are being understood to be widespread in PD and prompting diagnostic reclassification 7 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, up to 30% patients had social cognitive impairment prompting the authors to suggest the addition of a sixth subtype of minimal cognitive impairment in PD‐Mild Social Cognition Impairment. Cognitive assessment batteries that include social cognition assessment are being developed and were shown to pick up frontal impairments that may be missed by classical frontal lobe assessment batteries 7 …”
mentioning
confidence: 99%